2021
DOI: 10.1002/mawe.202000266
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microstructural defects and the surface topography on the fatigue behavior of “additively‐subtractively” manufactured specimens made of AISI 316L

Abstract: As additive manufacturing offers only low surface quality, a subsequent machining of functional and highly loaded areas is required. Thus, a sound knowledge of the interrelation between the additive and subtractive manufacturing process as well as the resulting mechanical properties is indispensable. In this work, specimens were manufactured by using laser‐based powder bed fusion (L‐PBF) with substantially different sets of process parameters as well as subsequent grinding (G) or milling (M). Despite the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(68 reference statements)
0
2
0
1
Order By: Relevance
“…In view of manufacturing methods, AMprocessing (e.g., PBF-LB) to a large extent pre-determines the achievable surface integrity, whereas post-processing primarily determines dimensional and geometrical form (e.g., roundness, flatness) accuracy, as well surface topography (surface form and texture). For example, Blinn et al showed that the AM process overrules the influence of postprocessing (milling and grinding) on fatigue life due to pronounced effects of AM-induced defects [235]. Functional performance hence obviously depends on material as well, i.e., 1) its constitutive properties and 2) material-processing properties (AM-induced surface integrity, e. g., internal porosity, bond failures, residual stresses and cracks).…”
Section: Functional Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In view of manufacturing methods, AMprocessing (e.g., PBF-LB) to a large extent pre-determines the achievable surface integrity, whereas post-processing primarily determines dimensional and geometrical form (e.g., roundness, flatness) accuracy, as well surface topography (surface form and texture). For example, Blinn et al showed that the AM process overrules the influence of postprocessing (milling and grinding) on fatigue life due to pronounced effects of AM-induced defects [235]. Functional performance hence obviously depends on material as well, i.e., 1) its constitutive properties and 2) material-processing properties (AM-induced surface integrity, e. g., internal porosity, bond failures, residual stresses and cracks).…”
Section: Functional Performancementioning
confidence: 99%
“…Removal of the surface and sub-surface defects using an appropriate machining process (within finishing range) was necessary to obtain reasonable fatigue performance for high-end applications where the parts are subjected to high alternating loads. Blinn et al [235] compared the HCF performance of PBF-LB/316L in as-built condition and after machining (milling and grinding) with that of continuously cast material subjected to similar finishing processes. In addition, two different printing strategies were examined to reveal the role of surface and sub-surface defects on the HCF before and after finishing processes.…”
Section: Lmentioning
confidence: 99%
“…Em termos de retificação, Yazdanpanah et al (2021) relataram uma melhora da rugosidade de 14,75 µm (SLMed) para 0,25 µm R a . Usando retificação pendular, Blinn et al (2021) reduziram a rugosidade inicial (após L-PBF) de 10,99±1,27 µm S a para 1,98±0,95 µm S a e 128,65±15,47 µm S z para 17,14±4,15 µm S z em cerca de 3,6 s. Usando retificação pendular e profunda, a rugosidade inicial (após laser-SLM) foi reduzida de 42-44 µm para 6,0 µm e 2,5µm R z , respectivamente (KIRSCH et al, 2020). Durante a fase de revisão sistemática da literatura, apenas três artigos supracitados avaliaram o impacto da retificação nas características superficiais de amostras de aço 316L fabricadas por MA.…”
Section: Fabricação (E Pós-processamento)unclassified